El Recurso de Casación y la garantía del derecho a un recurso amplio en los casos de Condena del Absuelto en el Código Procesal Penal de 2004 - Morales Aniceto, Jhanira Yamali (2018)
The present research work entitled: "The Appeal of Cassation and the guarantee of the right to a comprehensive remedy in the cases of Condemnation of the Absolved in the New Peruvian Processal of 2004 ", addresses the problem regarding the Condemnation of the Absolved, regulated in articles 419, inc.2 and 425, inc.3 literal b. The problem that has arisen is to determine if the Appeal of Cassation is the ideal way to guarantee the right to a broad appeal in the cases of Condemnation of the Absolved, in the New Peruvian Procedural Code in the years 2012 to 2017 and in order to contrast the hypothesis has been developed within the thematic theoretical framework such as, the theory of the challenge, the effective judicial protection, the resource of appeal and appeal of cassation, etc. The Inductive - Deductive, Comparative, Analytical - Synthetic method was also used in the analysis of the cases that have been the subject of study. This investigation has concluded mainly that the appeal is not the best way to guarantee the right to a wider appeal in case of conviction to the acquitted; because this remedy, because it is extraordinary, limited and inefficient, does not allow an adequate review of the conviction in the second instance, since the convicted person will not be able to request a review of the erroneous assessment of the factual and probative circumstances of the second instance conviction, as if the convicted person has it in the first instance, an issue that involves a cut of essential guarantees of due process.